Analisis Penggunaan Obat Antihipertensi di Poliklinik Rawat Jalan Rumah Sakit PMI Bogor: Perbandingan Cost Effectiveness dan Kualitas Hidup Pasien - ERNI RUSTIANI; RETNOSARI ANDRAJATI; LIANA ARSYANTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Hypertension is the main problem in Indonesia and all of the world. The primary goal of hypertension treatment is reduce the total risk of cardiovascular morbidity and mortality. The high prevalence of hypertension and the requirement of medications for prolonged periods, caused the drug- treatment cost represents a major issue in health economics. The aim of this study was to describe patients characteristic when using antihypertensive drugs in polyclinic PMI hospital Bogor, determine the most cost effective drugs for blood pressure reduced output and asses the influence of hypertensive treatments to quality of life, analyzed the relationship between cost effectiveness and quality of life. This research conducted a cross-sectional descriptive study. Analytical study was Cost Effectiveness Analysis (CEA). Data were collected from primary data (using SF-12 questionnaire) and secondary data (receipt, medical record and laboratory financial data). All data analyzed using SPSS for windows version 17. Of the 137 patient, most of them women (52.6%), average age 58.6 ± 11.4 years, range 28 – 87 year, most of the patients (51.1%) with comorbid conditions and combination therapy (50.4%) was used more commonly. Results of this study indicating that the most cost effective drugs for blood pressure reduced output was combination of Beta Blocker (BB) + diuretic. The outcome measures of cost effectiveness and patient quality of life are correlated with one another.